Aquatic refuges for surviving a global catastrophe. (May 2017) - Turchin, Alexey; Patrick Green, Brian
Highlights: Nuclear submarines could be effective refuges from several types of global catastrophes. Existing military submarines could be upgraded for this function with relatively low cost. Contemporary submarines could provide several months of surface independence. A specially designed fleet of nuclear submarines could potentially survive years or even decades under water. Abstract: Recently many methods for reducing the risk of human extinction have been suggested, including building refuges underground and in space. Here we will discuss the perspective of using military nuclear submarines or their derivatives to ensure the survival of a small portion of humanity who will be able to rebuild human civilization after a large catastrophe. We will show that it is a very cost-effective way to build refuges, and viable solutions exist for various budgets and timeframes. Nuclear submarines are surface independent, and could provide energy, oxygen, fresh water and perhaps even food for their inhabitants for years. They are able to withstand close nuclear explosions and radiation. They are able to maintain isolation from biological attacks and most known weapons. They already exist and need only small adaptation to be used as refuges. But building refuges is only "Plan B" of existential risk preparation; it is better to eliminate such risks than try to survive them.